2011
DOI: 10.1179/146701010x486417
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators in paediatric cochlear implant surgery: a systematic literature review

Abstract: Evaluation of relevant adverse prognostic factors in paediatric CI remains a largely unreported field. Better identification of these factors is required for improving vital pre-operative counselling and resultant surgical expectations and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 144 publications
0
33
0
1
Order By: Relevance
“…These were: late age of implantation, inner ear malformations and meningitis. In this review, connexin 26 (GJB2) mutations had a negligible impact (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These were: late age of implantation, inner ear malformations and meningitis. In this review, connexin 26 (GJB2) mutations had a negligible impact (14).…”
Section: Discussionmentioning
confidence: 99%
“…The IT-MAIS test for preverbal children and tests for early speech perception were used. Perception categories were assigned to results appropriate to the speech perception category (SPC), as described by Moog and Geers (14). The scale with six levels includes categories where 0 means there is no detection, 1 stands for detection only, 2 for pattern perception, 3 for inconsistent closed-set word recognition and multiple spectral differences, 4 for consistent closed-set word recognition of vowels, 5 for consistent closed-set word recognition of consonants and 6 for open-set word recognition.…”
Section: Speech Perception Evaluationmentioning
confidence: 99%
“…Indications for pediatric cochlear implantation are becoming more complex with an increase in bilateral implantation and a growing number of children with less severe hearing losses being implanted [10,[12][13][14][15]. Also, children with multiple medical conditions resulting from prematurity or perinatal etiologies are more likely to be considered as candidates, expanding the criteria for implantation even more [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic literature review on prognostic indicators in pediatric CI surgery, Black et al [10] identified only four factors influencing pediatric CI outcomes consistently, namely age at implantation, presence of inner ear malformations, as well as occurrence of meningitis and Connexin 26 GJB2 gene-related deafness. Firstly, early implantation is indisputably considered as a strong positive predictor of expressive and receptive language skills, as confirmed by a plethora of published studies [9,[18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation